JAMINAN KEPASTIAN HUKUM INVESTASI DI INDONESIA SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 6 TAHUN 2023 TENTANG CIPTA KERJA - Pandu Nugroho; M. Adib Ridwan Azizy (Universitas Karya Husada Semarang, 2023)
This writing discusses issues related to legal certainty for direct investment in Indonesia in the perspective of Law Number 25 of 2007 concerning Investment in the new Investment Regulations in Indonesia through Law Number 11 of 2020 concerning Job Creation ( hereinafter abbreviated as